PROGRAM INTERVENSI DALAM UPAYA PENURUNAN PREVALENSI TUBERCULOSIS PARU DI WILAYAH KERJA PUSKESMAS LEGOK - Michelle Angelika S; Yohanes Firmansyah; Liesia Asiku; Nicole Nastassja Kurniawan (Jurnal Medika Hutama, 2021)
Background: Based on the Global Burden of Disease study, TB is the second leading cause of death in the world. WHO 2017 is estimated to have 1,020,000 cases in Indonesia, but only 420,000 cases have been recorded at the Ministry of Health. The incidence of TB cases in Indonesia has never declined, there are still many cases that have not been reached and detected. Objective: To reduce transmission, morbidity and mortality rates for pulmonary tuberculosis in the Legok Health Center area. Methods: The research is a one group pre-post test with interventions and demonstration in the form of counseling and demonstration ethics of coughing and washing hands to improve public knowledge. at Posyandi Anggrek I Desa Serdang Wetan, Legok. The sample in this study was selected by non random consecutive sampling. The independent variables in this study were educational activities to increase student knowledge The dependent variables in this study were changes in knowledge. Results: 29 respondents (25 female and 4 male) had increased their knowledge after the intervension. 100% of respondents have an increase in knowledge in 20 aspects which are considered as indicators of knowledge Conclusion: Interventions conducted in the form of counseling, hand washing demonstrations, and cough ethics have succeeded in increasing public knowledge about pulmonary TB and it is hoped that in the future it will have an impact on improving people's attitudes and behavior in tackling and preventing pulmonary TB disease circulating in the community.